2019
DOI: 10.1101/671545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decomposition disentangled: a test of the multiple mechanisms by which nitrogen enrichment alters litter decomposition

Abstract: 281. Nitrogen (N) enrichment has direct effects on ecosystem functioning by altering soil abiotic 29 conditions and indirect effects by reducing plant diversity and shifting plant functional 30 composition from dominance by slow to fast growing species. Litter decomposition is a key 31 ecosystem function and is affected by N enrichment either by a change in litter quality (the 32 recalcitrance of the plant material) or through a change in soil quality (the abiotic and biotic 33 components of the soil that affe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 62 publications
(11 reference statements)
2
20
0
Order By: Relevance
“…These results were in agreement with those of previous studies (McLaren and Turkington 2010;Zhao et al 2017). A large number of studies have found that there is a close correlation between the initial N content and N-related indicators, especially C: N and lignin: N, which are considered as evident indicators for predicting the litter decomposition rate (Mooshammer et al 2012;Pichon et al 2020). This may be the reason that the leaf litter of broad-leaved species had a slower decomposition rate than the fine roots, while the opposite result was found for coniferous species (Fig.…”
Section: Effect Of Litter Type and Species On The Bacterial Diversitysupporting
confidence: 92%
“…These results were in agreement with those of previous studies (McLaren and Turkington 2010;Zhao et al 2017). A large number of studies have found that there is a close correlation between the initial N content and N-related indicators, especially C: N and lignin: N, which are considered as evident indicators for predicting the litter decomposition rate (Mooshammer et al 2012;Pichon et al 2020). This may be the reason that the leaf litter of broad-leaved species had a slower decomposition rate than the fine roots, while the opposite result was found for coniferous species (Fig.…”
Section: Effect Of Litter Type and Species On The Bacterial Diversitysupporting
confidence: 92%
“…Plots were mown once in the middle of June and once in August (see Supplementary Methods and Pichon et al . 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The mean volumetric water content of 5.95% indicated rather dry conditions when we collected the samples for the present study (mean from June to August 2017). Further information about the design of PaNDiv and field characteristics can be found in Pichon, Cappelli, Soliveres, Hölzel, et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The use of functional traits has revolutionised community ecology and allowed a more mechanistic and predictive understanding of these compositional shifts and therefore of how plant communities respond to global change (Allan et al, 2015; Lavorel & Grigulis, 2012; McGill et al, 2006; de Vries et al, 2012). At the same time functional traits have been shown in many studies to be good predictors of ecosystem functioning (Allan et al, 2015; Cappelli et al, 2020; Díaz et al, 2007; Lavorel & Grigulis, 2012; Pichon, Cappelli, Soliveres, Hölzel, et al, 2020; Ratcliffe et al, 2017; Roscher et al, 2013), although weaker effects have also been observed (van der Plas et al, 2020). Mean plant trait values therefore simultaneously respond to global changes and affect ecosystem functioning, and changes in functional trait composition may be a major mechanism explaining global change effects on functioning (Allan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%